Collaboration analysis among stakeholders in strengthening the export-oriented ceramic industry centre: study in Puwakarta Regency in Indonesia. (22nd May 2019) - Raharja, Sam'un Jaja; Rivani, Rivani; Arifianti, Ria
This study uses the collaboration perspective to describe and analyse the roles and relationships among stakeholders in the ceramic industry centre in Purwakarta Regency. This research used the qualitative method and data were collected through literature review, field observation and interviews. Results show the following conditions of the existing ceramics industry in Purwakarta: 1) export is generally through an export agent; 2) the majority of the human resources are unskilled and with low education; 3) operation and production activities are constrained by technology and raw materials; 4) financial aspects have difficulty in accessing financial institutions. Moreover, results of the research related to the role and relationships among stakeholders show that the stakeholder roles, tasks, influence and interest vary from extremely strong to weak. Each stakeholder has a different power, tasks and interest, works independently and has yet to establish a permanent collaboration with other stakeholders.